Chasing Quality TVET Curricula - Bhandari, Usha (Journal of Technical and Vocational Education and Training, 2025)
The curriculum serves as the backbone of any educational system which is crucial in shaping individuals and fostering desirable skills. In the realm of Technical and Vocational Education and Training (TVET), a well-structured curriculum not only equips learners with skills and competencies to meet industry demands but also enhances productivity and help combat poverty. However, many TVET initiatives often fail to achieve their goals due to inadequate curriculum development. This paper aims to delineate the fundamental components of a high-quality TVET curriculum, exploring definitions and key attributes, and discussing effective curriculum development models, including the frameworks forwarded by Tyler, Taba, and Wheeler. Furthermore, it evaluates three distinct curriculum types - traditional, outcome-based, and competency-based - highlighting the relevance of the competency-based approach for TVET. This model’s emphasis on practical skills, real-world applicability, and alignment with industry standards positions it as the most effective method to prepare students for the workforce. Ultimately, the paper underscores the necessity of continuous engagement with industry stakeholders and adaptability in curriculum design to empower learners and foster sustainable development within society.